2010
DOI: 10.1266/ggs.85.273
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis for flowering time using backcross population between Oryza sativa Nipponbare and O. rufipogon

Abstract: In the near future, global average temperature is expected to increase due to the accumulation of greenhouse gases, and increased temperatures will cause severe sterility in many crop species. In rice, since wild species show high genetic variation, they may have the potential to improve the flowering characters of cultivars. In this study, we investigated flowering characters under natural conditions by comparing an Asian wild rice accession of Oryza rufipogon W630 (originated from Myanmar) with a Japanese ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Two wild rice accessions have been used to map the QTL for EMF. Thanh et al (2010) made the first attempt using the mapping population of nipponbare/O.…”
Section: Genetic Analyses For Emf Traitmentioning
confidence: 99%
See 1 more Smart Citation
“…Two wild rice accessions have been used to map the QTL for EMF. Thanh et al (2010) made the first attempt using the mapping population of nipponbare/O.…”
Section: Genetic Analyses For Emf Traitmentioning
confidence: 99%
“…Japanese cultivars, Hatsuboshi (Iida et al, 2002;Wakamatsu et al, 2007) and Hinohikari (Wakamatsu et al, 2007(Wakamatsu et al, , 2008, are known as susceptible cultivars, while Hana-echizen (Kobayashi et al, 2007), Koshijiwase (Iida et al, 2002;Tabata et al, 2007), Fusaotome (Tanaka et al, 2010;Wakamatsu et al, 2008), Kokoromachi (Shirasawa et al, 2013), Chikushi52 , and Genkitsukushi rufipogon. Three QTLs for EMF were detected on chromosomes 4, 5, and 10, indicating that the alleles of O. rufipogon shifted FoT to 30 min earlier than nipponbare (Thanh et al, 2010). Another attempt was made by Hirabayashi et al (2015), using O. officinalis as a donor parent.…”
Section: Genetic Variation In Heat Tolerance To Wbcgmentioning
confidence: 99%
“…Peak flowering in this study was considered when 50% of the spikelets were opened (Thanh et al 2010). …”
Section: Peak Of Floweringmentioning
confidence: 99%
“…These microsatellite markers can be possibly linked or associated to the start of flower opening time for the EMF trait in rice. Similarly, Thanh et al (2010) using backcross population, identified QTL for starting time when the first spikelet opened (SOTb) on chromosome 5, with markers flanking RM249-RM440. These results indicate that chromosomes 5, 7, 8, 9, and 11 were most likely the possible QTL locations for peak flowering time, time when most of the flowers are closed and time when all of the flowers are closed.…”
Section: Qtl Analysis For the Early Morning Flowering (Emf) Traitsmentioning
confidence: 99%
See 1 more Smart Citation